Estudo fitoquímico de Salacia elliptica (Mart.) G.Don (Celastraceae), síntese de derivados do lupeol e avaliação de atividades biológicas - Elizabeth Luciana Marinho Miguel (2024)
In this study, the phytochemical and biological investigation of the roots of Salacia elliptica (Celastraceae) is presented. This includes the extraction and characterization of essential oils from the leaves and branches of the same species, as well as the synthesis and evaluation of biological activities of lupeol-derived esters. The phytochemical analysis of the roots led to the identification of ten constituents, among which eight were identified as friedelane-type pentacyclic triterpenes: friedelan-3-one (SE01), friedelan-3β-ol (SE02), a mixture of friedelan-3β-ol (SE02) and friedelan-1,3-dione (SE03), friedelan-3,15-dione (SE05), 15α-hydroxyfriedelan-3-one (SE06), 15α,26-di-hydroxyfriedelan-3-one (SE08), 26-hydroxyfriedelan-3,15-dione (SE09), and 7α,15α-di-hydroxyfriedelan-3-one (SE10). Additionally, a steroid, spinasterol (SE07), and a mixture of fatty acids (SE04) were identified. The pentacyclic triterpene SE10 is novel in the literature. The ethyl acetate and methanol extracts were analyzed by UHPLC-ESI-MS/MS, revealing the putative identification of 14 compounds, predominantly polyphenols such as flavonoids (chalcone, flavanone, flavone, and flavonoid benzoquinone). The essential oil from the leaves was obtained, and structural propositions for 17 compounds were made, with the main constituents being pentadecane, hexan-1-ol, and (Z)-hex-3-en-1-ol. Similarly, structural propositions for 13 compounds were made for the essential oil from the branches, with the main constituents being caryophyllene oxide, 10-epi-junenol, and oleamide. Lupeol derivatives were synthesized through Steglich esterification, resulting in 20 lupeol esters. Seventeen of these are novel, including lupeol 4-bromobenzoate (EL01), lupeol 2-bromobenzoate (EL02), lupeol naproxenate (EL03), lupeol 3-iodobenzoate (EL04), lupeol 10-undecenoate (EL05), lupeol 4-pentynoate (EL06), lupeol 3-thiophenoate (EL07), lupeol 2-indolate (EL08), lupeol α-methylcinnamate (EL09), lupeol 2,4-difluorobenzoate (EL10), lupeol naphthoate (EL11), lupeol 5-chlorosalicylate (EL12), lupeol 4-methylthiazole-5-ate (EL15), lupeol 2-bromo-5-methoxybenzoate (EL16), lupeol 3,5-bis(trifluoromethyl)benzoate (EL17), lupeol 2-hydroxy-5-methoxybenzoate (EL18), and lupeol 2,4-dichlorophenoxyacetate (EL19). Additionally, three compounds known in the literature were obtained: lupeol 4-nitrobenzoate (EL13), lupeol nicotinate (EL14), and lupeol benzoate (EL20). Yields varied between 83% and 4%. The biological testing involved the evaluation of cytotoxicity of isolated compounds SE01, SE02, SE06, SE08, SE09, and esters EL01, EL02, EL04, and EL07 against the A549 lung cancer cell model analyzed through flow cytometry. All exhibited significant cytotoxic activity, comparable to that exhibited by the triterpene lupeol (IC50 = 19,92). Additionally, compounds SE01, SE02, SE06, SE08, chloroform, ethyl acetate, and methanol extracts, and esters EL01, EL02, EL03, EL04, EL05, EL06, EL07, and EL08 were tested for in vitro antifungal activity against strains of Candida, Cryptococcus, and Sporothrix. However, none of the compounds or extracts showed activity at the tested concentrations.